2023
DOI: 10.3390/ijms242417545
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NKG2D and Its Ligands in Autoimmune Diseases: New Targets for Immunotherapy

Leiyan Wei,
Zhiqing Xiang,
Yizhou Zou

Abstract: Natural killer (NK) cells and CD8+ T cells can clear infected and transformed cells and generate tolerance to themselves, which also prevents autoimmune diseases. Natural killer group 2 member D (NKG2D) is an important activating immune receptor that is expressed on NK cells, CD8+ T cells, γδ T cells, and a very small percentage of CD4+ T cells. In contrast, the NKG2D ligand (NKG2D-L) is generally not expressed on normal cells but is overexpressed under stress. Thus, the inappropriate expression of NKG2D-L lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 139 publications
0
2
0
Order By: Relevance
“…This finding implies MICA plays an essential part in the onset of autoimmune inflammatory illnesses. Additionally, a growing list of evidence indicates that NKG2D-positive CD4+ T cells and NK cells contribute to the pathogenesis of SLE and RA through interactions with MICA and sMICA/B [ 14 ]. Accordingly, NKG2D and NKG2D-L are important therapeutic targets in the treatment of autoimmune disorders by blocking the interaction between NKG2D of immune cells and MICA on non-immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…This finding implies MICA plays an essential part in the onset of autoimmune inflammatory illnesses. Additionally, a growing list of evidence indicates that NKG2D-positive CD4+ T cells and NK cells contribute to the pathogenesis of SLE and RA through interactions with MICA and sMICA/B [ 14 ]. Accordingly, NKG2D and NKG2D-L are important therapeutic targets in the treatment of autoimmune disorders by blocking the interaction between NKG2D of immune cells and MICA on non-immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although immunotherapy was initially and most extensively applied in the field of oncology, as research has revealed that virtually all diseases have some form of direct or indirect relation with the immune system, the scope of immunotherapy has extended beyond cancer treatment. It now encompasses therapies aimed at inducing, enhancing, or suppressing the patient’s own immune response to treat a wide array of diseases related to immune molecules, immune cells, and the immune system itself, including infectious diseases (such as sepsis) ( 26 ), autoimmune diseases (such as systemic lupus erythematosus) ( 27 , 28 ), and diseases related to immunosenescence and inflammaging (such as atherosclerosis, Alzheimer’s disease, and diabetes) ( 29 32 ). It is commonly accepted that the core pathophysiological mechanism of sepsis involves a dysregulated immune response characterized by acute-phase hyperinflammation followed by late-phase immune suppression, triggered by pathogens.…”
Section: Introductionmentioning
confidence: 99%